2001
DOI: 10.1097/00006842-200105000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Activation in Patients With Irritable Bowel Syndrome and Control Subjects During Rectosigmoid Stimulation

Abstract: IBS patients show altered brain responses to rectal stimuli, regardless of whether these stimuli are actually delivered or simply anticipated. These alterations are consistent with reported alterations in autonomic and perceptual responses and may be related to altered central noradrenergic modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
185
3
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(209 citation statements)
references
References 55 publications
14
185
3
7
Order By: Relevance
“…Several human studies also showed activation in the striatum in response to CRD [5,52,63] or gastric distention [37] in normal subjects. Neuroanatomical evidence suggests that nociceptive information may reach the basal ganglia through several afferent sources including the medial and posterior thalamus, amygdala, PBN area, dorsal raphe nucleus, as well as cortical regions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several human studies also showed activation in the striatum in response to CRD [5,52,63] or gastric distention [37] in normal subjects. Neuroanatomical evidence suggests that nociceptive information may reach the basal ganglia through several afferent sources including the medial and posterior thalamus, amygdala, PBN area, dorsal raphe nucleus, as well as cortical regions.…”
Section: Discussionmentioning
confidence: 95%
“…In healthy human subjects, amygdala activation has been reported in response to gastric dis-tension [42], whereas decrease in activation has been reported in response to CRD (at least in female subjects) [5,11,52,63], though these studies have not provided information on subnuclei. In patients with IBS both increased activation [11] and no change [5,52,63] have been reported in response to CRD. The discrepancy may be attributable to differences in the experimental design and differences in CRD delivery parameters.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Functional imaging studies using positron emission tomography and fMRI revealed that patients with IBS often have exaggerated activation of cerebral sensory areas, especially emotional areas of brain following visceral stimulation as compared to healthy subjects. [12][13][14][15][16][17][18][19][20] Evidence from these studies indicates differential activation of the anterior cingulate cortex (ACC), prefrontal cortex (PFC), thalamus, insular cortex, and other limbic brain regions during colorectal stimulation, heterotopic stimulation or rectal balloon distension in IBS patients compared with healthy subjects. [12][13][14][15]18 Furthermore, resting state fMRI study performed on IBS patients demonstrated increased spontaneous neuronal activity in visceral afferent processing regions, while decreased regional brain activity in cognitive and pain regulatory regions.…”
Section: Introductionmentioning
confidence: 99%
“…В исследовании [5] по-лучены данные, что у пациентов с СРК -носителей гена 5-HTTLPR отмечается увеличение регионального кровотока в го-ловном мозге в ответ на растяжение кишечника, особенно выра-женное в коре орбитофронтальной области. Аналогичные ре-зультаты в ответ на стимуляцию ректосигмоидного отдела ки-шечника получены и в другом исследовании [24]. Принимая во внимания эти данные, можно отметить, что у пациентов с СРК повышение болевой чувствительности кишечника сопровожда-ется повышением активности участков мозга, ответственных за эмоциональную сферу.…”
Section: терапевтический архив 8 2015unclassified